2014
DOI: 10.18043/ncm.75.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Utilization in the North Carolina Medicaid Population With a Focus on “High Exposure” Patients, 2007–2012

Abstract: purpose We examined trends in utilization of computed tomography (CT) among Medicaid enrollees in North Carolina, the clinical setting in which those CT scans were performed, and the number of enrollees known to have undergone 10 or more scans in a given year. methods North Carolina Medicaid claims were analyzed to determine the number of CT studies performed between January 1, 2007, and December 31, 2012. We assessed the number of "high exposure" patients-those who received 10 or more CT scans in a given cale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…We used Medicaid claims data to extract patient demographic characteristics and limited clinical information for all Medicaid patients in North Carolina who had claims for 10 or more CT scans during 2010; we also collected claims data for these patients for the year following the intervention-July 1, 2011, through June 30, 2012 (fiscal year [FY] 2012). For more detailed information about the types of CT scans included in this study and an explanation of how the scans were counted, readers can refer to the article by Burke and colleagues on pages 95-101 of this issue [27].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used Medicaid claims data to extract patient demographic characteristics and limited clinical information for all Medicaid patients in North Carolina who had claims for 10 or more CT scans during 2010; we also collected claims data for these patients for the year following the intervention-July 1, 2011, through June 30, 2012 (fiscal year [FY] 2012). For more detailed information about the types of CT scans included in this study and an explanation of how the scans were counted, readers can refer to the article by Burke and colleagues on pages 95-101 of this issue [27].…”
Section: Methodsmentioning
confidence: 99%
“…In 2012 our analyst rewrote the query to account for most of these exceptions; however, some of the inpatient claims were still bundled in such a way that they were not accessible to queries. We found that our original count of 640 high-exposure patients (shown in Figure 1) was too low; when we reran our query, we found that 2,646 Medicaid patients without a cancer diagnosis had 10 or more CT scans in 2010 [27]. All CT scan counts presented in …”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The widely diffused use of MDCT for different clinical purpose, however, increases patient and population radiation exposures [2]. Different concerns are consequently emerging about appropriateness, resource utilisation and possible biological costs in terms of radiation exposure.…”
Section: Introductionmentioning
confidence: 99%